Public Relations Management of Universities in Yasni Institute of Islamic Religion Muara Bungo - Bodi Kurniawan; Bedjo Sujanto; Suparno Eko Widodo (Syntax Corporation Indonesia, 2022)
Abstract This qualitative study aims to find out the duties, functions, and responsibilities of higher education institutions require interaction with the public as clients and partners, so that universities need to make internal improvements, among others through improved communication between the academic community to produce efficiency and effectiveness of higher education management. Public relation is an effort that consciously motivates people to be affected, especially through communication. It is necessary to formulate education management and marketing strategies for the community to maintain the image of the college, therefore it takes good planning, organizing, implementation, and control to achieve the desired goal. Keywords: Management, Public Relation, Image